A Review of the Eighth Forum of the World Association for Political Economy. (1st December 2013) - ,; ,
Abstract : There are many kinds of inequalities such as inequalities between nations, gender inequalities, racial inequalities, and especially income and wealth inequalities, which are emerging as the most important ones in the current global crisis of capitalism. Also, the latest historic crisis of capitalism has led to a decline in the levels of growth in the world, especially in Europe, with enormous social consequences. The response of the dominant classes in these countries to these problems has been the imposition of austerity policies. These policies instead of reducing unemployment and improving living standards have increased the reach of private capitalist activities. In May of 2013, WAPE held its Eighth Forum themed ""Inequalities and World Capitalism: Analysis, Policy and Action."" The aim is to analyze the reasons for world inequality and counter measures against it, find the conditions of the world development from the radical perspective through renewed study of the finished and unfinished writings of Marx and of the plural realities of our time.